Masked hypertension and submaximal exercise blood pressure among adolescents from the Avon Longitudinal Study of Parents and Children (ALSPAC). (22nd August 2019) - Huang, Zhengzheng; Sharman, James E.; Fonseca, Ricardo; Park, Chloe; Chaturvedi, Nish; Davey Smith, George; Howe, Laura D.; Lawlor, Deborah A.; Hughes, Alun D.; Schultz, Martin G.
Abstract : Purpose: Masked hypertension is associated with increased cardiovascular risk but is undetectable by clinic blood pressure (BP). Elevated systolic BP responses to submaximal exercise reveal the presence of masked hypertension in adults, but it is unknown whether this is the case during adolescence. We aimed to determine if exercise BP was raised in adolescents with masked hypertension, and its association with cardiovascular risk markers. Methods: A total of 657 adolescents (aged 17.7 ± 0.3 years; 41.9% male) from the Avon longitudinal study of parents and children (ALSPAC) completed a step‐exercise test with pre‐, post‐, and recovery‐exercise BP, clinic BP and 24‐hour ambulatory BP. Masked hypertension was defined as clinic BP <140/90 mm Hg and 24‐hour ambulatory BP ≥130/80 mm Hg. Assessment of left‐ventricular (LV) mass index and carotid‐femoral pulse wave velocity (aortic PWV) was also undertaken. Thresholds of clinic, pre‐, post‐, and recovery‐exercise systolic BP were explored from ROC analysis to identify masked hypertension. Results: Fifty participants (7.8%) were classified with masked hypertension. Clinic, pre‐, post‐, and recovery‐exercise systolic BP were associated with masked hypertension (AUC ≥ 0.69 for all, respectively), with the clinic systolic BP threshold of 115 mm Hg having high sensitivity and specificity and exercise BP thresholds of 126, 150, and 130 mm Hg, respectively, having high specificity and negative predictive value (individually or when combined) for ruling out the presence of masked hypertension. Additionally, this exercise systolic BP above the thresholds was associated with greater left‐ventricular mass index and aortic PWV. Conclusions: Submaximal exercise systolic BP is associated with masked hypertension and adverse cardiovascular structure in adolescents. Exercise BP may be useful in addition to clinic BP for screening of high BP and cardiovascular risk in adolescents.